2016
DOI: 10.1007/s00284-015-0969-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Hemagglutinin from Gallibacterium anatis

Abstract: Gallibacterium anatis has the ability to hemagglutinate rabbit erythrocytes; however, no bacterial component has yet been associated with this function. In the present work, a protein of approximately 65 kDa with hemagglutinating activity for glutaraldehyde-fixed chicken erythrocytes was purified by ion interchange chromatography from G. anatis F149(T) secreted proteins. The protein was recognized by a rabbit polyclonal serum against a hemagglutinin from Avibacterium paragallinarum. The 65 kDa purified protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…In contrast, the putative hemoglobin-binding protein (70-kDa protein from the culture without the added chelating agent) was at a higher concentration in samples from the F149 T strain, and a tiny band was observed in iron-restricted conditions ( Figure 4 ). G. anatis F149 T is a non-hemolytic and non-virulent strain with few studies on its participation in gallibacteriosis ( Montes-García et al, 2016 ; Zhang et al, 2017 ). However, this G. anatis strain also expresses different virulence factors as virulent strains do, but in a lower amount.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, the putative hemoglobin-binding protein (70-kDa protein from the culture without the added chelating agent) was at a higher concentration in samples from the F149 T strain, and a tiny band was observed in iron-restricted conditions ( Figure 4 ). G. anatis F149 T is a non-hemolytic and non-virulent strain with few studies on its participation in gallibacteriosis ( Montes-García et al, 2016 ; Zhang et al, 2017 ). However, this G. anatis strain also expresses different virulence factors as virulent strains do, but in a lower amount.…”
Section: Discussionmentioning
confidence: 99%
“…E. coli and Pseudomonas aeruginosa PAO1 were cultured in LB-broth to test siderophores production. G. anatis F114 and ESV34 strains hemolytic varieties ( Montes-García et al, 2016 ) were also included in this study. Several fur -mutant strains were obtained in this work, but the mutant assayed in vivo here was Ω fur 126.13.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different anti-sera against different proteins were used to determine their potential participation in biofilm formation: phosphoglycerate mutase (PGM), a protein functioning as afimbrial adhesin in A. seminis (Montes Garcı ´a et al 2018a); elongation factor Tu (EF-Tu) or hemagglutinin, both proteins previously described in Gallibacterium anatis biofilms (Montes Garcı ´a et al 2016;Lo ´pez-Ochoa et al 2017); OMP2-like from Mannheimia haemolytica; an amyloid-like protein found in M. haemolytica biofilm (Montes Garcı ´a et al 2018b); A. seminis biofilm matrix and sera from sheep with epididymitis. An overnight A. seminis culture was adjusted to 1.0 OD 600 nm, mixed with each antiserum (1:10), and incubated for 1 h under agitation.…”
Section: Effect Of Different Anti-sera On Biofilm Formationmentioning
confidence: 99%
“…Many of these FHA-like proteins act as adhesins, similar to FHA of B. pertussis, and some have been implicated in biofilm and aggregative growth, a precursor to biofilm (300,(357)(358)(359)(360)(361)(362)(363)(364).…”
Section: Introductionmentioning
confidence: 99%